Influence of incorporating dried fruits on dairy drinks characteristics focusing on their antimicrobial effects - Soliman, Neveen S M; Salam, Ayah B Abdel; Emam, Shimaa R; Orabi, Ahmed; Nader, Sara M; Saad, Mena (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study was designed to show the effect of adding different levels of dried fruit extracts for 14 days on sensory and chemical parameters in dairy drinks. The survival of Pseudomonas aeruginosa and Bacillus cereus in artificially contaminated dairy drinks fortified with these extracts was also studied. Materials and Methods: The freshly watery extracts and nonaqueous extracts of dried fruits were prepared by rotary evaporators and solvents, respectively. The determination of the minimum inhibitory concentration of dried fruit extracts was achieved using the disc diffusion test. The sensory evaluation of samples was done, while the chemical parameters of the examined samples were determined by the calibrated analyzer. In addition, the degree of survival of P. aeruginosa and B. cereus in inoculated milk samples was also estimated. Results: In pasteurized and Rayeb milk samples, the water extract of carob and all alcoholic dried fruit extracts had a significant effect on compositional parameters in comparison to control samples. At day 14 of pasteurized milk storage, the watery (20.0%) and alcoholic (10.0%) extracts of carob significantly improved its sensory parameters. Conclusion: Based on the survival results, all utilized dried fruit extracts had a significant inhibitory effect on P. aeruginosa and B. cereus growth in the fortified milk samples at the end of storage. This trial of the survival of these new dairy drinks is the first investigation, particularly in the Middle East. Extracts of utilized dried fruits have prospective functions that enhance dairy drink characteristics. Adv. Vet. Anim. Res., 11(1): 55-64, March 2024 http://doi.org/10.5455/javar.2024.k747